Instantaneous BeiDou+GPS RTK positioning with high cut-off elevation angles - Teunissen, Peter; Odolinski, Robert; Odijk, Dennis (Springer - Verlag, 2014)
As the Chinese BeiDou Navigation Satellite System (BDS) has become operational in the Asia-Pacific region, it is of importance to better understand as well as demonstrate the capabilities that a combination of BeiDou with GPS brings to positioning. In this contribution, a formal and empirical analysis is given of the single-epoch RTK positioning capabilities of such a combined system. This will be done for the single- and dual-frequency case, and in comparison with the BDS- and GPS-only performances. It will be shown that with the combined system, when more satellites are available, much larger than the customary cut-off elevations can be used. This is important, as such measurement set-up will significantly increase the GNSS applicability in constrained environments, such as e.g. in urban canyons or when low-elevation multipath is present.